2015
DOI: 10.1016/j.phpro.2015.05.055
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ZDDP Content and Thermal Decomposition in Motor Oils Using NAA and NMR

Abstract: Zinc dialkyldithiophosphates (ZDDPs) are one of the most common anti-wear additives present in commercially-available motor oils. The ZDDP concentrations of motor oils are most commonly determined using inductively coupled plasma atomic emission spectroscopy (ICP-AES). As part of an undergraduate research project, we have determined the Zn concentrations of eight commercially-available motor oils and one oil additive using neutron activation analysis (NAA), which has potential for greater accuracy and less sen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…Zhang et al [30] showed that the ageing process accelerated at high temperature and resulted in the higher formation of decomposition products. Ferguson et al [29] also showed that thermal decomposition of ZDDP occurs at temperatures as low as 150 °C. ZDDP decomposes to Zn and P compounds during the ageing process.…”
Section: Oil Degradation In Presence Of Cbmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [30] showed that the ageing process accelerated at high temperature and resulted in the higher formation of decomposition products. Ferguson et al [29] also showed that thermal decomposition of ZDDP occurs at temperatures as low as 150 °C. ZDDP decomposes to Zn and P compounds during the ageing process.…”
Section: Oil Degradation In Presence Of Cbmentioning
confidence: 99%
“…Moreover, as the ageing time increased from 2 to 96 h, higher concentration of zinc and phosphorous were observed on the CB particles. This is due to the thermal decomposition of ZDDP additives during the ageing process [29]. Zhang et al [30] showed that the ageing process accelerated at high temperature and resulted in the higher formation of decomposition products.…”
Section: Oil Degradation In Presence Of Cbmentioning
confidence: 99%
“…In the cases of II.e and III.e, where the lubricant temperatures are 100 and 120°C, respectively, the flash temperatures are found to be as high as 112°C in Case II.e and 133°C in Case III.e. Therefore, within the operating range of this study, the ZDDP anti-wear agent (lubricant additive), whose activation temperature is above 150°C [45], doesn't take effect. A set of preliminary RCF experiments using a four-cylinder contact set-up also showed no difference between the tests with and without the ZDDP additive.…”
Section: Resultsmentioning
confidence: 90%
“…Its dynamic viscosity was equivalent to 77.1 cSt (40 °C) and 11.6 cSt (100 °C), respectively. The concentration of ZDDP was ≈800 ppm in test engine oil . In this study, this engine oil was used as the base oil, which was ultrasonically blended with the defined amount of graphene for the preparation of formulated engine oil containing graphene.…”
Section: Methodsmentioning
confidence: 99%